Isolation of Epstein-Barr virus (EBV)-negative cell clones from the EBV-positive Burkitt's lymphoma (BL) line Akata: malignant phenotypes of BL cells are dependent on EBV. - Shimizu, N (1994)
During cultivation of the Epstein-Barr virus (EBV)-positive Burkitt's lymphoma (BL) line Akata, it was noted that EBV DNA is lost from some of the cells. Isolation of EBV-positive and EBV-negative clones with the same origin made it possible to examine the effects of EBV in BL cells. The results indicate that malignant phenotypes of BL, such as growth in low serum, anchorage-independent growth in soft agar, and tumorigenicity in nude mice, are dependent on the presence of EBV genomes and underline the oncogenic function of EBV in human cancer.